Properties of a singular value decomposition based dynamical model of gene expression data - Simek, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski)
Recently, data on multiple gene expression at sequential time points were analyzed using the Singular Value Decomposition (SVD) as a means to capture dominant trends, called characteristic modes, followed by the fitting of a linear discrete-time dynamical system in which the expression values at a given time point are linear combinations of the values at a previous time point.
Keywords: multiple gene expression; Singular Value Decomposition (SVD); dynamical model of gene expression data